Association of Aortic Stiffness With Cognition and Brain Aging in Young and Middle-Aged Adults: The Framingham Third Generation Cohort Study. Issue 3 (March 2016) - Pase, Matthew P.; Himali, Jayandra J.; Mitchell, Gary F.; Beiser, Alexa; Maillard, Pauline; Tsao, Connie; Larson, Martin G.; DeCarli, Charles; Vasan, Ramachandran S.; Seshadri, Sudha
Abstract : Aortic stiffness is associated with cognitive decline and cerebrovascular disease late in life, although these associations have not been examined in young adults. Understanding the effects of aortic stiffness on the brain at a young age is important both from a pathophysiological and public health perspective. The aim of this study was to examine the cross-sectional associations of aortic stiffness with cognitive function and brain aging in the Framingham Heart Study Third Generation cohort (47% men; mean age, 46 years). Participants completed the assessment of aortic stiffness (carotid–femoral pulse wave velocity), a neuropsychological test battery assessing multiple domains of cognitive performance and magnetic resonance imaging to examine subclinical markers of brain injury. In adjusted regression models, higher aortic stiffness was associated with poorer processing speed and executive function (Trail Making B–A; β±SE, −0.08±0.03; P <0.01), larger lateral ventricular volumes (β±SE, 0.09±0.03; P <0.01) and a greater burden of white-matter hyperintensities (β±SE, 0.09±0.03; P <0.001). When stratifying by age, aortic stiffness was associated with lateral ventricular volume in young adults (30–45 years), whereas aortic stiffness was associated with white-matter injury and cognition in midlife (45–65 years). In conclusion, aortic stiffness was associated with cognitive function and markers of subclinical brain injury in young to middle-aged adults. Prospective studies are needed to examine whether aortic stiffening in young adulthood is associated with vascular cognitive impairment later in life. Abstract : Supplemental Digital Content is available in the text.